The Effects of Different Levels and Sources of Oil on Production Performance, Reproduction, Blood Metabolites and Nutrients Digestibility of Kurdish Ewes - Masood Didarkhah; Moosa Vatandoost (پژوهشهای علوم دامی ایران, 2023)
Introduction: One of the most important problems in the sheep breeding industry is its low reproduction capacity. According to the advances made in the field of reproduction, new methods have led to the improvement of the reproduction process. One of the important and effective indicators in reproduction is the level of energy used in the diet during the reproductive season. The use of fat supplements in the diet increases the energy density, and by reducing the inhibitory effects of the negative energy balance, it improves reproductive and productive performance. The right amount of oil consumption guarantees health and food safety. It is recommended that 10% or less of the energy needed by the body per day comes from saturated fat sources and 20-35% of daily energy comes from unsaturated fat. Due to the importance of oil seeds, their cultivation is also very important and they have a wide cultivated area all over the world. The purpose of this research was to investigate the effects of levels and sources of oil and fat on reproductive performance and blood factors of Kurdish sheep.Materials and Methods: The experiment was conducted at the Research Unit Farm of the Light Livestock Breeding Shightogan Delaware Company, located in the southern Khorasan province, Iran. Fifty-six ewes with Non-pregnant with an average age of one year and average body weight of 41.35±2.5 kg were divided into 7 treatments and 8 replications for 60 days (habituation period 14 days). Experimental treatments include: 1- base diet without oil, 2- Basic ration containing 2% sunflower oil, 3- Basic ration containing 2% canola oil, 4- Basic ration containing 2% tallow, 5- Basic ration containing 4% sunflower oil, 6- Basic ration containing 4% canola oil and 7- Basic ration It contained 4% tallow. Estral synchronization was performed in spring with CIDR. Ewes after CIDR (14 day) extraction and PMSG injection as soon as the signs of estrus were observed, the ewes were isolated from the others and artificially inseminated with fresh sperm using the transcortical method. Energy and chemical composition of rations were similar and were examined simultaneously with CIDR removal and estrus observation. Then, in each experiment parameters such as the time of estrus initiation (hour), rate of return to estrus, parturition rate, rate of multiple births, number of lambs and rate of lambing were evaluated Body weight (BW) and body growth measures were recorded First and period End. Data obtained were analyzed by statistical software SAS (version 1.9). Estral synchronization was performed in spring with CIDR. Ewes after CIDR (14 day) extraction and PMSG injection as soon as the signs of estrus were observed, the ewes were isolated from the others and artificially inseminated with fresh sperm using the transcortical method. The nutrition program with software (SRNS) version was adjusted based on the pregnancy diet.Results and Discussion: The results showed that the highest pregnancy rate (100%) and lambing rate (125%) were related to ewes receiving rations with 2% tallow oil and 4% sunflower oil. The highest increase in body weight was observed in ewes consuming ration with 2% sunflower oil, which was significantly different from the control group. But with other groups, this difference was insignificant. The highest body weight gain and the best (lowest) feed conversion ratio were observed in ewes consuming 2% sunflower oil diet, which was significantly different from the control group. But with other groups, this difference was insignificant. Triglyceride concentration, plasma total protein concentration and plasma albumin were not affected by oil and fat sources in the diets and no significant difference was observed between the diets. There was a significant difference in the average apparent digestibility coefficients of dry matter, crude fat and organic matter of nutrients between treatments.Conclusion: In general, use of vegetable and animal oils in the diet can positive effect on the productive and reproductive performance of sheep results of this research showed that in order to reduce the rate of consumption costs, 2% in the ration is suggested.